Risk Factors for Concussion in Under 18, Under 22 and Professional Men's Rugby Union: A Video Analysis of 14,809 Tackles - Takayuki Kawasaki; Yuta Kawakami; Shuko Nojiri; Yoshinori Hasegawa; Manabu Kuroki; Shogo Sobue; Kenta Shibuya; Yuji Takazawa; Muneaki Ishijima (SpringerOpen, 2023)
Abstract Objective This study aimed to identify the risk factors for tackle-related concussion observed in matches involving under (U) 18, U 22 and professional men's Rugby Union players through video analysis. Study Design Descriptive epidemiology study. Methods Twenty Rugby Union matches each for high school (U18), university/college (U22) and professional (Elite) were randomly selected from 202 matches in the 2018/2019 season. Both one-on-one and tackles involving multiple tacklers were analyzed for the 60 matches. The 28 categorical and continuous variables (e.g., tackle characteristics and duration before the tackle) were applied as risk factors to a least absolute shrinkage and selection operator (Lasso) regression analysis. To identify high-risk situations, a simulation model with coefficients obtained from the Lasso regression was used. Statistical analysis was conducted according to tackle direction. Results A total of 14,809 tackles and 41 concussions involving 1800 players were included in the analyses. The incidence rate of concussions (injuries/1000 tackles) was greater in Elite players (4.0) compared with U18 (1.9) and U22 (2.4) players. The factors most highly associated with concussions were head-in-front tackles (where the tackler's head is placed forward, impeding a ball carrier's forward movements, 11.26/1000 tackles), and were more often observed among U18 players. A simulation model predicted that the highest risk tackle situation in Elite players was a head-in-front, side-on tackle below the hip of the ball carrier (predicted incidence rate 18.07/1000 tackles). Conclusion The risk factors associated with concussion need to be assessed cautiously. Avoiding head-in-front, side-on tackles to the lower extremities of a ball carrier should be considered to reduce injury risks.